Propedeutics of internal medicine: tests for final knowledge control for the practical classes and individual work for 2nd year students of international faculty (speciality 221 «Dentistry») - Mykhailovska, N. S.; Grytsay, A. V.; Stetsiuk, I. O.; Konovalova, M. O.; Manujlov, S. M.; Михайловська, Наталія Сергіївна; Грицай, Ганна Володимирівна; Стецюк, Ірина Олегівна; Коновалова, Марія Олександрівна; Мануйлов, Сергій Миколайович (Запорізький державний медико-фармацевтичний університет, 2023)
Tests compiled in accordance with the program of « Propedeutics of internal medicine ». Guidelines are intended to help students prepare for practical classes and learn the material. Can be used for training of 2nd years students of international faculty, speciality 221 «Dentistry».